CAM Modalities Can Stimulate Advances in Theoretical Biology. Issue 1 (2005) - Hankey, Alex
Abstract : Most complementary medicine is distinguished by not being supported by underlying theory accepted by Western science. However, for those who accept their validity, complementary and alternative medicine (CAM) modalities offer clues to understanding physiology and medicine more deeply. Ayurveda and vibrational medicine are stimulating new approaches to biological regulation. The new biophysics can be integrated to yield a single consistent theory, which may well underly much of CAM—a true 'physics of physick'. The resulting theory seems to be a new, fundamental theory of health and etiology. It suggests that many CAM approaches to health care are scientifically in advance of those based on current Western biology. Such theories may well constitute the next steps in our scientific understanding of biology itself. If successfully developed, these ideas could result in a major paradigm shift in both biology and medicine, which will benefit all interested parties—consumers, health professionals, scientists, institutions and governments.